The Questionnaire Development for the Strategic Leadership Components of Prosthetic and Orthotic Practitioners in Thailand - มโนเพ็ชรเกษม ธัชนันท์; กาญจนวงศ์ สุรีย์; จันทรังษี ไพศาล (Journal of The Royal Thai Army Nurses, 2018)
Qualitative research method was used in this study. The objective of this study was to develop a questionnaire for Strategic Leadership of Prosthetic and Orthotic Practitioners in Thailand. The methods of study were to synthesize concepts, theories, related research, focus group discussion and in-depth interview. Informants were administrators as well as prosthetic and orthotic practitioners who have been working in medical institutes, secondary-level and tertiary-level hospital. Twenty informants were purposely selected for focus group discussion and 8 informants were selected for in-depth interview. Content validity was measured by using Index of Item-Objective Congruence (IOC) and Content Validity Index (CVI). Reliability was measured by using Cronbach alpha coefficient The synthesis of research results revealed that there were 7 components of strategic leadership of prosthetic and orthotic practitioners in Thailand including; (1) Strategic thinking and planning; 14 items, (2) Developing today’s and tomorrow’s leader; 10 items (3) Relating the part to the whole; 15 items, (4) Making it happen; 7 items, (5) Releasing corporate spirit; 6 items, (6) Giving direction; 7 items, and (7) Building partnership; 6 items. Totally, there were 65 items. As a questionnaire was developed based on those components, it was brought to test content validity. The results showed that the value of IOC for each item was .96 as well as the value of CVI = 0.81. Reliability of the questionnaire was tested by using Cronbach alpha coefficient and it was found that α = 0.98. From the research findings, it be suggested that the questionnaire should be taken further to confirm with the empirical data.